Project management circa 2025 - Cleland, David I.; Bidanda, Bopaya (Project Management Institute, 2009)
Presents a series of essays on the future of project management, discussing new techniques and tools which might be needed and examining opportunities for its use in such areas as energy development, extreme weather response, and climate control.